Humanitarian Innovation Guide - and ELHRA (2018)
The Humanitarian Innovation Guide is a growing online resource to help individuals and organisations define humanitarian problems and successfully develop innovative solutions. ABOUT THE GUIDE The humanitarian sector is investing in exciting innovations, but it is not yet producing a steady pipeline of well-designed solutions that effectively address problems, evidence their impact, and have the potential to be scaled. As stated in a recent independent evaluation of the Humanitarian Innovation Fund (Triple Line, 2017), a review of the innovation ecosystem in 2015 found significant gaps in resources for innovation, including a shortage of guidance on the skills needed to manage successful innovation projects. These findings were echoed in the research carried out to inform this resource. As part of a grant agreement with the European Commission to provide financial and technical support to emerging humanitarian innovations, and in line with our strategic aim to develop the sector’s skills and capabilities in humanitarian innovation, this resource aims to translate our own learning, along with learning from across the sector, into a practical, grounded guide for innovators working in humanitarian contexts. Building on our unique position in the sector, the Humanitarian Innovation Guide is designed to provide targeted support to individuals and organisations attempting to develop innovative solutions to the challenges facing humanitarian assistance, resulting in a more effective humanitarian response. The Guide is written with two audiences in mind: humanitarian practitioners who are seeking to develop a new approach to their work and want to apply an innovation lens to solving problems; and social entrepreneurs from outside the sector who have identified an opportunity to engage with the sector and need a humanitarian framework to contextualise their innovation plans. We also hope that it will be a useful resource for innovation managers who are tasked with supporting innovation in their agencies, labs or networks. As the first step-by-step guide to managing innovation in the humanitarian sector, we hope that its continued development will better enable individuals, organisations and the wider sector to: Plan the activities involved in an innovation process and systematise the management of innovation. Manage a successful innovation project and generate evidence for innovation. Ensure that innovations are developed in an ethical way, with full consideration of risks and responsibilities.